Surgical Management and Outcomes of Extremity Vascular Trauma - Madhur Kumar; Anubhav Gupta (Indian Journal of Vascular and Endovascular Surgery)
Background: The majority of patients with traumatic extremity injury often present late in developing countries. Various factors such as ischemia time, level of arterial injury, the extent of soft-tissue disruption, and efficiency of collateral supply had been implicated for limb loss. The present study aims to evaluate management strategies and outcomes along with factors dictating limb salvage in peripheral vascular trauma. Materials and Methods: Fifty patients with peripheral vascular trauma who met the inclusion criteria during the 1-year study period (August 2018–July 2019) were included in the study. Data were analyzed by categorizing all study subjects into limb salvage and amputation groups. Results: Of all subjects, 84% of patients suffered blunt trauma. All the patients underwent revascularization beyond the “golden period” of 6 h. The majority of patients underwent primary repair (72%) versus interposition vein graft (28%). Postoperatively, the limb salvage rate was 92%. Secondary amputation was necessitated following popliteal artery injury due to blunt trauma. Multivariate logistic regression identified early graft failure as a significant factor for limb loss (P = 0.025). Conclusion: The delayed presentation should not deter the need for vascular repair. Early graft failure was significantly associated with limb loss.